2018
DOI: 10.5114/pjr.2018.78624
|View full text |Cite
|
Sign up to set email alerts
|

Coronary age, based on coronary calcium measurement, is increased in patients with morbid obesity

Abstract: PurposeObesity is a well-known of risk factor for atherosclerosis. However, recently an “obesity paradox” has been discussed, which is considered as a protective effect of obesity on the development coronary artery disease (CAD). An aim of the study was to investigate the risk of CAD in morbidly obese patients using coronary artery calcium measurement.Material and methodsFifty-one patients with morbid obesity (BMI ≥ 40 kg/m2) and thirty controls were scanned to determine the amount of coronary artery calcifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In support of the role of obesity as a coronary risk factor, one study detected significantly higher prevalence of CAC in obese than in non-obese (39) and CAC score of 1-99 AU predict high-risk plaque (40). Moreover, it was found that bariatric surgery for severe obesity significantly reduces the future risk of developing CV comorbidities with significant reduction in CAC scores (41).…”
Section: Resultsmentioning
confidence: 98%
“…In support of the role of obesity as a coronary risk factor, one study detected significantly higher prevalence of CAC in obese than in non-obese (39) and CAC score of 1-99 AU predict high-risk plaque (40). Moreover, it was found that bariatric surgery for severe obesity significantly reduces the future risk of developing CV comorbidities with significant reduction in CAC scores (41).…”
Section: Resultsmentioning
confidence: 98%